Guest-induced structural transformation of single-crystal 3D covalent organic framework at room and high temperatures - Aiping Yao; Hongliang Xu; Kuizhan Shao; Chunyi Sun; Chao Qin; Xinlong Wang; Zhongmin Su (Nature Communications)
Abstract Soft porous crystals, recognized as the third generation of smart porous materials, can undergo structural deformations in response to external stimuli, such as temperature, pressure, and guest molecules. Currently, the dynamic phase transformations of soft porous crystals are predominantly determined through quantitative modeling based on gas adsorption and powder X-ray diffraction. Herein, we investigate the single-crystal-to-single-crystal structural transformation of covalent organic soft porous crystal modeled on COF-300 and identified nine distinct conformational isomers induced by different guest molecules at room and high temperatures. Notably, COF-300 can maintain its single-crystal structure even at 280 °C and efficiently absorbs polycyclic aromatic hydrocarbons in their molten state. The kinetics of structural transformations among conformational isomers are investigated by combining PXRD and theoretical calculations. The structural transformation from a high-energy state to a low-energy state is a rapid, energetically favorable process, while the reverse transformation is a slow process driven by concentration gradients.